2011
DOI: 10.1007/s12199-011-0233-y
|View full text |Cite
|
Sign up to set email alerts
|

Determination of whether the association between serum albumin and activities of daily living in frail elderly people is causal

Abstract: This 2-year cohort study has demonstrated that a decrease in serum albumin levels is associated with a decrease in ADL levels. A third factor may play a role in adversely affecting both serum albumin and ADL levels in frail elderly people.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
20
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 11 publications
3
20
0
Order By: Relevance
“…For some authors there is a direct link between albumin concentration and strength loss over two years [40], whilst in other studies this association presented no statistical significance [34,41].…”
Section: In Community Dwelling and In Nursing Homementioning
confidence: 91%
See 3 more Smart Citations
“…For some authors there is a direct link between albumin concentration and strength loss over two years [40], whilst in other studies this association presented no statistical significance [34,41].…”
Section: In Community Dwelling and In Nursing Homementioning
confidence: 91%
“…Thus, in elderly people with functional disability and albumin <35 g/L it was found that malnutrition prevalence was 70%, whilst in autonomous elderly people with albumin concentrations >35 g/L, the prevalence of malnutrition was only 13% [31][32][33][34][35][36].…”
Section: In Hospitalized Elderlymentioning
confidence: 96%
See 2 more Smart Citations
“…The association between the ability to perform basic activities of daily living and albumin has been studied recently, noting a direct correlation between poor functional status and lower levels of albumin [10]. Backgrounds and aims: To analyze whether serum cholesterol and albumin may be factors associated with early and late mortality, independent from other variables such as comorbidity, functional and mental status, in very old patients admitted with acute illness.…”
Section: Introductionmentioning
confidence: 99%